Evaluating the effects of road hump on noise level and vehicles speed at IIUM Institutional area - Aziz, Hassanuddin; Kadar Hamsa, Abdul Azeez (Eastern Asia Society for Transportation Studies (EASTS), 2017)
Noise pollution is among the most prominent environmental problems encountered in every aspect of daily life. This paper investigates the effects of road hump on the noise level and speed of vehicle specifically on a major road in International Islamic University Malaysia (IIUM). Spot speed and noise level was collected by selecting two road humps with different design profiles on-campus. Two points at each road hump, one at the road hump and the other 15 m after the road hump were selected for the measurement of speed and noise level. The findings show that there is significant difference in noise level and speed of vehicles on and after the road humps. It is noted that redesign of the road hump especially its height is needed to ensure that the vehicles can cross the road hump without increasing noise level and vehicle speed unnecessarily especially immediately after the road hump.